A STUDY DHARMA TOPIC TO SYNTHESIZE FO MINDFULNESS’S PATTERN : WATPHAJAREANRAT LUMLOOKKA DISTRICT PATHUMTANEE PROVINCE - Gotiram, Chompoo; Keawbunjan, Panya; Keawboonjan, Sureeporp; Janpensri, Supanya (Journal of Graduate MCU KhonKaen Campus, 2021)
The objectives of this research were (1) to study synthesize Dharma Topic Related with mindfulness and (2) to study a Place of thammastanvimol and (3) to synthesize the pattern of mindfulness.This research is qualitative research. The instrument for collecting data were interview, observation and discussion.The result of data analysis research was relialibity and consistent with the objective of research The research results are as below: Buddhist principles related to mindfulness consist of development (pawana), training (trisikkha),problem solving to both physical (social) and mental. Mental management to be conscious and able to dominate oneself and with wisdom (mindfulness), in order to have a normal physical life and mental for peace circumspection and wisdom. A mindfulness are both theory and training. CharoenRat monastery is suitable for mental management. Synthesized the Buddhist principles that is Satipatthana to be pattern of mindfulness for monastery and coorperate for mindfulness